2021
DOI: 10.1038/s41598-021-01933-9
|View full text |Cite
|
Sign up to set email alerts
|

A pan-cancer analysis revealing the role of TIGIT in tumor microenvironment

Abstract: T cell immunoreceptor with immunoglobulin and ITIM domain (TIGIT), an immune checkpoint, plays a pivotal role in immune suppression. However its role in tumor immunity and correlation with the genetic and epigenetic alterations remains unknown. Here, we comprehensively analyzed the expression patterns of the TIGIT and its value of prognostic prediction among 33 types of cancers based on the data collected from The Cancer Genome Atlas (TCGA) and the Genotype-Tissue Expression projects (GTEx). Furthermore, the c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 74 publications
1
19
0
Order By: Relevance
“…TIGIT overexpression has been found in the cellular microenvironment of several tumors, including lung ( 111 ), kidney ( 112 ), liver ( 113 ), glioma ( 114 , 115 ), melanoma ( 116 ), colorectal carcinomas ( 117 ), gastric cancer ( 118 ), and neuroblastomas ( 119 ). TIGIT expression was found to be strongly associated with poor prognosis in colorectal cancer and positively correlated with pathological stages in renal clear cell carcinoma ( 120 ), kidney renal papillary cell carcinoma, and uveal melanoma ( 121 , 122 ).…”
Section: Tigit In Cancer Progressionmentioning
confidence: 99%
“…TIGIT overexpression has been found in the cellular microenvironment of several tumors, including lung ( 111 ), kidney ( 112 ), liver ( 113 ), glioma ( 114 , 115 ), melanoma ( 116 ), colorectal carcinomas ( 117 ), gastric cancer ( 118 ), and neuroblastomas ( 119 ). TIGIT expression was found to be strongly associated with poor prognosis in colorectal cancer and positively correlated with pathological stages in renal clear cell carcinoma ( 120 ), kidney renal papillary cell carcinoma, and uveal melanoma ( 121 , 122 ).…”
Section: Tigit In Cancer Progressionmentioning
confidence: 99%
“…Several studies have highlighted the suppressive impact of TIGIT on a wide range of immune functions and immune cells (e.g., T/NK cells) 163 165 . Besides, TIGIT + Treg cells selectively inhibit pro-inflammatory Th1 and Th17 cell responses, but not Th2 cell responses 166 .…”
Section: Discussionmentioning
confidence: 99%
“…We extracted the DEGs of these two groups of COAD to screen the genes that perform an instrumental function in tumors. The results of pathway enrichment suggest that the pathways involved by these genes are concentrated in Cell adhesion molecules (CAMs) ( Bronikowska et al, 2021 ), cytokine receptor interaction ( Wen et al, 2021 ), focal adhesion ( Lu et al, 2021 ), NF kappa B signaling pathway ( Takakura et al, 2021 ), proteoglycans in cancer ( Jinmin Sun et al, 2021 ), PI3K Akt signaling pathway ( Xue et al, 2021 ), etc, which are strongly associated with to the onset and progression of tumors. Further cluster analysis showed that CryptLike, EMT, Collective and Proliferative were distributed in different modules respectively.…”
Section: Discussionmentioning
confidence: 99%